Assesing interactivity in the websites of human rights organizations' websites in Egypt - Fahmy, Andalib Mohamed (AUC Knowledge Fountain, 2015)
The Internet has many advantages over the other media in the provision of information services especially in the field of human rights. In Egypt the image of the human rights organization has been affected severely after the Egyptian revolution due to continuous media attack on them; therefore, it became vital to change this image. As the websites is the primary tool that permits the organizations to connect with their audience and permit the audience to know their activities, analyzing the websites of the human rights in Egypt from user perspective become vital This study aims to assess the interactivity and public involvement allowed by the sites to see whether they use their websites in an efficient way that permit them to reach their audience nationally and internationally or not, moreover, it tries to figure out reasons behind this level of interactivity. â€œReception based analysisâ€ technique was used for the first time in Egypt, to map both the interactivity level and the amount of public engagement allowed by the site in a sample of 10 existing human rights websites along with Heeter and Burgeon 7 dimensions of interactivity (content and availability of choice, effort user must exert, responsiveness to users, ease of adding information, facilitation of interpersonal communication, modality and information rich, and ability to make two ways communication ) ; Moreover , interviews with experts and official working in the field of human rights was used to know more in depth data about the barriers that confront the websites developers of human rights organizations in Egypt Using the reception based analysis technique gives the study the advantage of understanding how the users sees different dimensions of interactivity and public engagement in the websites of human right NGOs. The results of the analysis indicated the overall level of opportunities for interactivity in the websites of human rights NGOs in Egypt is very low; moreover, the overall level of public engagement allowed by the site is low. Moreover, the results of the interviews revealed that lack of funds, lack of media and IT specialists in the organization, and technological gap were the main problems that confront the organization while maintaining interactivity of their website.